2015
DOI: 10.1186/s12866-015-0343-6
|View full text |Cite
|
Sign up to set email alerts
|

CsrA impacts survival of Yersinia enterocolitica by affecting a myriad of physiological activities

Abstract: BackgroundA previous study identified a Yersinia enterocolitica transposon mutant, GY448, that was unable to export the flagellar type three secretion system (T3SS)-dependent phospholipase, YplA. This strain was also deficient for motility and unable to form colonies on Lauria-Bertani agar medium. Preliminary analysis suggested it carried a mutation in csrA. CsrA in Escherichia coli is an RNA-binding protein that is involved in specific post-transcriptional regulation of a myriad of physiological activities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…coli and Y . enterocolitica have demonstrated that CsrA promotes motility by activating expression of the FlhDC regulators [ 30 , 47 ]. Thus, through concerted ablation of motility and adaptation of PNAG synthesis regulatory cascades, the Y .…”
Section: Discussionmentioning
confidence: 99%
“…coli and Y . enterocolitica have demonstrated that CsrA promotes motility by activating expression of the FlhDC regulators [ 30 , 47 ]. Thus, through concerted ablation of motility and adaptation of PNAG synthesis regulatory cascades, the Y .…”
Section: Discussionmentioning
confidence: 99%
“…Free CsrA controls expression of the two important colonization factors invasin (InvA) and PsaA through the RovM-RovA regulatory cascade [5,9,10] (Figure 1). Deletion of csrA also abolishes the motility of Y. pseudotuberculosis and Y. enterocolitica, as CsrA is required for translation of the flagella master regulator flhDC [5,11]. Flagellar motility is required for efficient adhesion and subsequent invasion into host cells [12].…”
Section: Trans-acting Rnas Of Yersiniamentioning
confidence: 99%
“…A microarray analysis further demonstrated that multiple genes of the virulence plasmid associated Ysc type III secretion system are differentially expressed in a csrA mutant of Y. pseudotuberculosis [13]. Furthermore, the Csr system is implicated in the control of biofilm formation, resistance against antibiotic, osmotic, and heat stress, as well as numerous metabolic pathways [11,13,14]. A major feature is that CsrA adjusts the central carbon flow through the pyruvate-acetate node and the tricarboxylic acid cycle in response to nutrient availability [13].…”
Section: Trans-acting Rnas Of Yersiniamentioning
confidence: 99%
“…A detailed expression analysis further revealed that in contrast to the Salmonella Csr system, both CsrB and CsrC are counter-regulated and respond to different TCS in response to metabolites (UvrY/BarA-CsrB) or ions (PhoP/PhoQ-CsrC) and are oppositely controlled by the Crp protein ( Heroven et al, 2008 ; Nuss et al, 2014 ). Apart of its influence on the RovM-RovA-InvA regulatory cascade, the Yersinia Csr system and Crp are part of a large adaptive response network, adjusting metabolic, and physiological processes, stress adaptation and virulence gene expression in response to changing environmental conditions ( Heroven et al, 2012a ; LeGrand et al, 2015 ; Nuss et al, 2015 ; Vakulskas et al, 2015 ). A recent study elucidated a tight connection between pathogenicity and core metabolism by integrated transcriptome and 13 C-fluxome analysis of Y. pseudotuberculosis , and identified the pyruvate-TCA cycle node as a focal point for controlling the host colonization and virulence of Yersinia which is tightly controlled by the interplay of Crp and the Csr system ( Bücker et al, 2014 ).…”
Section: Regulatory Circuits Controlling Early Stages Of Host Colonizmentioning
confidence: 99%
“…A genetic screen led to the identification of the transcriptional regulator IscR, which modulates gene transcription depending on the coordination of its 2Fe–2S clusters which can be influenced by oxidative stress, oxygen limitation, or iron availability ( Miller et al, 2014 ). Similar to the Salmonella v-T3SS regulator HilD, LcrF expression seems also under control of several conserved TCSs: (i) the Rcs phosphorelay which is used to adapt their cell physiology in response to perturbations of the cell envelope ( Li et al, 2015 ), (ii) the BarA/UvrY(SirA) controlling the Csr system in response to carbon sources ( LeGrand et al, 2015 ), and (iii) the CpxAR system that responds to extra-cytoplasmatic stress ( Liu et al, 2012 ). As mentioned above (see Regulation of Motility), LcrF synthesis is also under negative control of the flagellar sigma factor FliA/σ 28 , and this inverse regulation of flagellar and v-T3SS genes ensures that expression of the immune defense apparatus is repressed when Yersinia uses flagellar motility to colonize external habits at temperatures below 30°C ( Horne and Pruss, 2006 ).…”
Section: Regulatory Circuits Controlling Early Stages Of Host Colonizmentioning
confidence: 99%